Ovarian Tumor in a Mare-Thecoma-Case Report - Prestes, Nereu Carlos [UNESP]; Nogueira de Moraes, Carolina [UNESP]; Maia, Leandro [UNESP]; de Oliveira, Isabelle Rayanne Sousa [UNESP]; Fabris, Viciany Erique; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2013)
Thecomas are tumors originating from the ovarian stroma and of rare occurrence in the equine species. Clinical, ultrasonographic, endocrine, and histopathologic descriptions of thecoma are scarce. This article aims to describe a case of ovarian changes in a mare with anomalous growth of the right ovary and anestrus for 1 year. After surgical removal, the ovarian growth was diagnosed as a thecoma. Histopathological findings were consistent with the findings previously described in the literature, characteristic of a thecoma, and decisive for the correct diagnosis. © 2013 Elsevier Inc.
Keywords: Anestrous; Histopathologic; Mare; Ovarian tumor; Thecoma; Equidae